Предмет: Алгебра,
автор: Lobnensky
Помогите пожалуйста =)
Ответы
Автор ответа:
0
Решение:
3^(5x+1) + 3^(5x-1)=30
3^5x*3^1 + 3^5x*3^-1=30
3*3^5x + 3^5x/3=30 Приведём уравнение к общему знаменателю 3
3*3*3^5x + 3^5x=3*30
9*3^5x + 3^5x=90
10*3^5x=90
3^5x=90 : 10
3^5x=9
3^5x=3^2
5x=2
х=2:5
х=2/5
Ответ: х=2/5
3^(5x+1) + 3^(5x-1)=30
3^5x*3^1 + 3^5x*3^-1=30
3*3^5x + 3^5x/3=30 Приведём уравнение к общему знаменателю 3
3*3*3^5x + 3^5x=3*30
9*3^5x + 3^5x=90
10*3^5x=90
3^5x=90 : 10
3^5x=9
3^5x=3^2
5x=2
х=2:5
х=2/5
Ответ: х=2/5
Похожие вопросы
Предмет: Литература,
автор: Аноним
Предмет: Русский язык,
автор: Guler08
Предмет: Литература,
автор: Аноним
Предмет: Литература,
автор: 333dasha